Pengaruh Belanja Modal, Pendapatan Asli Daerah Dan Angkatan Kerja Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Di Provinsi Kalimantan Barat - B01111121, Prezi (Jurnal Pembangunan dan Pemerataan, 2016)
The effect of capital expenditure, the local revenue and the labor force to the economic growth of the Regency / City in the Province of West Kalimantan. Â  This research aimed to analyze the effect of capital expenditure, the local revenue and the labor force to the economic growth of the Regency / City in the Province of West Kalimantan. This research uses quantitative analysis is to determine the effect of capital expenditure, the local revenue and the labor force to economic growth in the District / City of West Kalimantan Province in 2009-2013. This research uses panel resource analysis in the 14 districts / city in the province of West Kalimantan in 2009-2013. Further data is regressed using Fixed Effect models, and statistical analysis tools Hausman test and statistics test. These results indicate that the variable capital expenditure, local revenue and the labor force have a positive and significant effect on economic growth in the District / City in the province of West Kalimantan. While the statistical t-test and f-test statistics of all the variables have a significant effect on economic growth, the coefficient of determination (R2) is 0.751096, which means the amount of influence exerted by the variable capital expenditure, local revenue and the labor force to the economic growth of the Regency / City in West Kalimantan by 75,1096%, while the remaining 24,8904% in the influence of other factors. Keyword: The Capital Expenditure, The Local Revenue, The Labor Force and the Economic Growth.